Light-emitting diode (LED) binding wire and method for manufacturing LED binding wire

By using high-purity silver alloy bonding wires, the high-temperature/conditional temperature intensity ratio and reflectivity are optimized, and the problem of difficulty in taking into account brightness and resistance in the process of miniaturization and thinning of LED devices is solved, and an efficient LED device design is achieved.

CN119604970APending Publication Date: 2025-03-11TANAKA DENSHI KOGYO KK
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380052349.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-14
Filing Date
2023-06-26
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the process of miniaturization and thinning, it is difficult to take into account the improvement of brightness and resistance to temperature changes and stress changes in the existing LED devices, and there are trade-offs on the reflectivity and heat resistance of the bonding wires.

Method used

A silver alloy bonding wire composed of more than 98% silver is used to optimize the high-temperature/conditioning temperature intensity ratio and the reflectivity of blue light, the heat resistance strength of the ball neck is improved, and the high reflectivity is maintained in ultra-low annular bonding.

Benefits of technology

The miniaturization and brightness of LED devices are achieved, while enhancing the resistance to temperature changes and stress changes, reducing production costs, and improving the long-term reliability of LED devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604970A_ABST
    Figure CN119604970A_ABST
Patent Text Reader

Abstract

Provided are: a silver alloy bonding wire for LEDs, which achieves a high reflectance with respect to blue light and which improves the heat-resistant strength of a ball neck part even in ultra-low ring-shaped bonding; and a method for manufacturing the silver alloy bonding wire for LEDs. The bonding wire for a light-emitting diode (LED) according to an embodiment is composed of a silver alloy containing 98 mass% or more of silver, and has a high-temperature / normal-temperature strength ratio of 0.6-0.99, and a high-temperature elongation of 1.5% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a bonding wire for a light emitting diode (LED), and more particularly to a bonding wire for a white LED used in a backlight of an LCD (liquid crystal display) and a method for manufacturing the same. In addition, the present invention relates to an LED device using the bonding wire for LED. Background Art

[0002] In recent years, light emitting diodes (LEDs) have been widely used. LEDs are light emitting elements made by combining P-type semiconductor materials and N-type semiconductor materials. Products in which light emitting elements are formed into various packages are also called LEDs. Sometimes, products formed into packages are also called LEDs (or LED devices), and light emitting elements are called LED elements to distinguish them. In this specification, unless otherwise specified, light emitting elements are called "LED elements" and products formed into packages are called "LED devices."

[0003] LED elements of red, orange, yellow-green, etc. were put into practical use after the 1950s. Taking advantage of the characteristics of small and low-power LED elements, they were used in indicators, information display boards, and displays of electronic equipment. In 1993, blue LED elements that light up brightly were put into practical use. In 1996, yellow phosphors that emit yellow light were combined with blue LED elements to complete quasi-white light-emitting LEDs that emit white light (hereinafter referred to as "white LEDs") . White LEDs have attracted attention as lighting, and are now rapidly popularizing with a trend that surpasses previous lighting fixtures such as incandescent lamps and fluorescent lamps. Since lighting fixtures using white LEDs can be expected to have a higher power saving effect than previous lighting fixtures, they have attracted attention as lighting fixtures that achieve energy saving in the lighting field, which accounts for a large part of domestic electricity consumption, with the increase in power saving awareness after the Great East Japan Earthquake in March 2011. After that, white LEDs are visually bright, so they are widely used in various lighting applications, such as general household bulb-type LED lamps, facility lighting, outdoor lighting, and car headlights.

[0004] As white LEDs for lighting become more common, LED devices have been improved in many ways, such as high luminous flux, miniaturization, and low cost. As a result, the use of LED devices has continued to expand. LED devices that have been developed in miniaturization have been adopted as backlights for liquid crystal displays (LCDs).

[0005] In recent years, LCDs have been widely used as display devices for various electronic devices and information terminals, such as televisions, personal computers (PCs), digital cameras, tablet terminals, smartphones, smart watches, car navigation devices, and drive recorders. In response to various uses, improvements in performance in many aspects are required.

[0006] For example, LCD panels with a brightness of 700cd to a maximum of 4000cd have been developed, which is much brighter than the 300cd for indoor use. This high-brightness LCD panel has high visibility in bright environments with sunlight, so it is suitable for display panels for display windows and outdoor advertisements. With the rapid spread of smartphones and smart watches, the use environment has expanded, and the demand for high visibility in outdoor sunlight has increased. For example, for smartphone use, a 520cd / m 2 Brightness of LCD panel.

[0007] The use environment of LCD panels has also become more diverse, not only for outdoor use where they are exposed to wind and rain, but also for indoor use. For example, LED devices used in car navigation devices and driving recorders must not only withstand the constant vibrations of driving a car, but also be able to adapt to harsh environments such as driving in cold regions to tropical regions, or on asphalt in hot weather.

[0008] The trend of miniaturization and thinning of electronic devices and information terminals equipped with LCD panels is also significant, and the miniaturization and thinning of LED devices mounted on them has also accelerated rapidly in recent years. For example, in 2013, a backlight LED device with a thickness (thickness in the light-emitting direction) of about 0.8mm was developed for small and medium-sized LCDs, but in recent years, the thickness of LED devices has reached about 0.6mm (where the thickness of the area that can be wire-bonded is about 0.3mm or less).

[0009] As described above, in recent years, there has been a significant demand for LED devices that can achieve both improved brightness and reduced size and thickness and can adapt to harsh environments for LCD backlight applications.

[0010] Here, the principle and structure of white LEDs, the structure of LED devices for LCD backlights, and the problems they have are explained.

[0011] The principle and structure of ordinary white LEDs for lighting or backlighting are as follows. If the blue light with a wavelength of about 450nm emitted from the blue LED element is absorbed by the yellow phosphor, yellow light of about 590nm, which is in a complementary color relationship, will be emitted. The yellow light emitted from the yellow phosphor is mixed with the blue light that is not absorbed by the phosphor, and visually appears to be white. The LED device of the white LED is a structure in which the upper surface of the LED element is sealed with a transparent resin (silicone resin, epoxy resin) containing a phosphor. Among white LEDs, there are vertical light-emitting diodes in which the pad electrodes of the blue LED element and the lead electrodes on the circuit board are arranged orthogonally, and horizontal light-emitting diodes in which they are arranged in parallel. At present, in addition to the yellow phosphor, green phosphors that emit green light and red phosphors that emit red light are combined to develop white LEDs for lighting with various color reproductions.

[0012] There are two types of LCD backlights: "direct type" and "edge type". "Direct type" is a form in which multiple LED light sources are arranged on a plane parallel to the LCD panel on the opposite side of the visible surface of the LCD panel so that the light from the light source is incident vertically on the LCD panel plane. Since the light from the light source is irradiated to the entire surface of the LCD panel, a realistic sense of detail and rich color reproduction can be obtained. "Edge type" is, for example, a form in which one or more LED light sources are arranged near the edge (edge) of the LCD panel so that the light from the light source is incident parallel to the LCD panel plane, and a reflective structure and a light-guiding structure are used to irradiate the light onto the entire LCD panel. Compared with the direct type, the edge type has poorer sense of detail and color reproduction, but it is easy to make the panel smaller and thinner, and the power consumption is also reduced. In addition, in LED devices used for backlight, low cost and brightness (high luminous flux) are important, and high precision and high visibility of the LCD panel are achieved by improving brightness.

[0013] Here, the structure of an LED device for LCD backlight is described. Figure 1 The cross section of an LED device 10 is schematically shown. The LED device 10 is an example of a surface-mounted LED device used for a conventional edge-type backlight. Figure 1The LED device 10 shown has a package substrate 9, an LED element 1 provided on the package substrate 9, a bank 6 surrounding the LED element 1, a bonding wire 3, and a pair of pad electrodes 21, 22 provided on the LED element 1. The LED device 10 further has lead electrodes 81, 82, and the bank 6 and the lead electrodes 81, 82 form a concave portion with the bank 6 as a side surface and the lead electrodes 81, 82 as a bottom surface, and the LED element 1 is placed on the bottom surface of the concave portion via an adhesive layer 7 composed of silver paste or the like. The lead electrodes 81, 82 are formed of aluminum or the like, and are bonded to the package substrate 9 by silver paste or the like. The pair of pad electrodes 21, 22 and the lead electrodes 81, 82 are electrically connected via the bonding wire 3. The LED element is covered with a sealing member 4. The sealing member 4 is, for example, a thermosetting resin such as epoxy resin, silicone resin, epoxy-modified silicone resin, or modified silicone resin. The sealing member 4 contains a phosphor (not shown) that converts the wavelength of light from the LED element 1.

[0014] Figure 1 The LED device shown is an example of an LED device before the miniaturization and thinning process was promoted. In this LED device, the loop shape of the bonding wire is generally a "high loop shape" in which the height of the loop from the electrode is relatively high, or a "special loop shape" in which a part of the loop is bent, compared with LED devices that have been miniaturized and thinned in recent years. For example, in the high loop shape, the loop height (h) is designed to be at least 4 to 5 times the wire diameter. In contrast, in LED devices that are miniaturized and thinned, a "low loop shape" is adopted in which the height of the loop from the electrode is even lower.

[0015] In the past, the bonding wire used to connect the pad electrode of the blue LED element and the lead electrode on the circuit board used a gold (Au) bonding wire with high electrical conductivity and good adhesion to the electrode. However, with the advancement of high output and high efficiency of LED devices, in order to improve the heat dissipation efficiency, a bonding wire composed of silver with a higher thermal conductivity than gold is used. As an Ag alloy bonding wire, a silver alloy bonding wire containing a specified amount of copper (Cu), platinum (Pt), gold (Au), palladium (Pd), nickel (Ni), chlorine (Cl), zinc (Zn), tin (Sn), rhodium (Rh), osmium (Os), rare earth elements, etc. in silver according to the desired purpose and characteristics is known (for example, refer to patent documents 1 to 3).

[0016] Prior art literature

[0017] Patent Literature

[0018] Patent Document 1: Japanese Patent Application Laid-Open No. 2012-099577

[0019] Patent Document 2: Japanese Patent Application Laid-Open No. 2013-110410

[0020] Patent Document 3: Japanese Patent Application Laid-Open No. 2014-096403 Summary of the invention

[0021] Problem that the invention aims to solve

[0022] As mentioned above, in recent years, there has been a significant demand for LED devices that can balance the improvement of brightness with miniaturization and thinness, and can adapt to harsh environments for LCD backlight applications. In this regard, the operating environment of LEDs used for lighting is relatively mild, and the demand for miniaturization is difficult to increase. In order to obtain brightness that is not inferior to that of fluorescent lamps, the luminous flux of each LED device is designed to be relatively high, at 180 (lm) to 1800 (lm). This is because, in order to obtain this high luminous flux, it is necessary to adopt methods such as expanding the area of ​​​​the LED element, or increasing the number of LED elements installed in the lighting, and increasing the current (forward current) that makes the LED element emit light.

[0023] In contrast, the luminous flux of each LED device used for LCD backlight is designed to be lower than that of LED devices used for lighting, with a maximum of about 20 (lm). As electronic equipment and information terminal equipment become smaller and thinner, the space for configuring LED devices is more limited, so it is extremely difficult to increase the luminous flux of LED devices by expanding the area of ​​​​LED elements. In addition, as electronic equipment and information terminal equipment become smaller and thinner, the heat dissipation of LED devices decreases, so it is also very difficult to increase the luminous flux of LED devices used for LCD backlight by increasing the forward current.

[0024] In addition, the high luminous flux (brightness improvement) and high brightness of LED devices achieved by improving the light-emitting LED elements themselves have also reached their limits. Therefore, in order to achieve high luminous flux and high brightness of LED devices for LCD backlight, the performance of peripheral parts of LED elements such as seals and bonding wires is improved to prevent the light from LED elements from attenuating.

[0025] For example, in an LED device, a bonding wire crosses a portion of the LED element above the light emitting surface (see Figure 1 ), the reflection and absorption of light on the bonding wire reduces the light output to the outside. In particular, for high-purity gold (Au) of 99.99% by mass or more, the gold (Au) element itself has a low reflectivity, which causes the appearance of a dark shadow on the bonding wire, reduces the visual white efficiency, or reduces the brightness of the LED device. In contrast, in a bonding wire composed of pure silver (Ag) with high reflectivity or a silver alloy close to pure silver, it can prevent the brightness of the LED from decreasing, and is cheaper than gold, so it is expected to be helpful in realizing bright LEDs at low cost.

[0026] However, pure silver (Ag) and silver alloy bonding wires are less resistant to temperature and stress changes than gold and lack durability. For example, in applications such as car navigation equipment and driving recorders that are exposed to heat and vibration in harsh environments, in addition to miniaturization and thinning of LED devices, strong impact resistance and high durability are required. In order to miniaturize and thin LED devices, it is necessary to wire LED elements in closer areas, and a high degree of freedom in wiring design is required for bonding wires. However, for wires with low resistance to temperature and stress changes, when a wiring structure with many bends in a narrow area is formed, failures caused by temperature and stress changes are prone to occur.

[0027] Therefore, although high reflectivity can be obtained in wires with improved silver purity, it will cause practical problems in miniaturized LED devices. However, if alloy elements are included in pure silver to reduce the purity of silver, a decrease in reflectivity is inevitable. From this, it can be seen that there is a trade-off between resistance to temperature changes and stress changes and high reflectivity, which will restrict the design of white LEDs aimed at miniaturization, thinning and improved brightness. It can even be said that the restrictions brought by the unique problems of bonding wires to the expansion of the use of white LEDs with great potential may have an adverse impact on major technological innovations in the future.

[0028] However, as described below, this trade-off problem cannot be solved by conventional Ag alloy bonding wires, which has brought technical constraints to the development of LED devices. The negative impact of technical constraints on the development of LED devices is immeasurable, and silver alloy bonding wires for LEDs are necessary to achieve resistance to temperature changes and stress changes while maintaining the brightness of white LEDs.

[0029] For example, Patent Documents 1 to 3 are documents that attempt to solve the problems in previous high-loop bonding. In the silver alloy bonding wire that requires ultra-low loop, there is no disclosure about the method of suppressing fatigue failure of the ball neck and improving resistance to repeated temperature changes and stress changes as described below.

[0030] It should be noted that the required properties of bonding wires for LEDs and bonding wires for ICs (integrated circuits) and LSIs (large-scale integrated circuits) are different. As described below, the bonding wires for LEDs are required to have resistance to unique temperature changes and stress changes. The thermal expansion coefficient of the transparent silicone resin used in the seal of LED devices is, for example, 200ppm / K to 400ppm / K, which is much larger than the thermal expansion coefficient of the epoxy resin used in the seal of IC and LSI devices (for example, about 6ppm / K to 40ppm / K). In addition, in order to reduce the thermal expansion coefficient to a value close to that of the silicon chip, the seal of IC and LSI devices is usually filled with inorganic micro-organic silicone (silicon oxide) fillers, but in the seal of LED devices, inorganic micro-organic silicone fillers are usually not filled. This is because, when the inorganic micro-organic silicone filler is filled in the seal of the LED device, the inorganic micro-organic silicone filler will reduce the light transmittance of the seal, thereby reducing the brightness of the LED. As a result, the thermal expansion change of the seal of the LED device is forced to become larger than that of the seal of the IC device and LSI device. The bonding wire embedded in the sealing material is exposed to repeated stress caused by expansion and contraction of the sealing material. Therefore, the bonding wire for LED is required to maintain higher resistance (fatigue resistance) to repeated temperature changes and stress changes than the bonding wire for IC.

[0031] Therefore, in order to obtain a silver alloy bonding wire that maintains the brightness of white LEDs while achieving resistance to temperature changes and stress changes, the inventors conducted a comparative study on the adverse conditions of conventional LED devices using high-loop and special-loop bonding during long-term use, and the adverse conditions of LED devices using low-loop or ultra-low-loop bonding to achieve miniaturization and thinness, together with their structures. As a result, it was found that these adverse conditions have the following differences.

[0032] First, the main problem in conventional LED devices using high-loop and special-loop bonding is fatigue failure of the wedge neck of the silver alloy bonding wire (the part that stands up in the wedge-shaped bonding with the lead electrode). A photograph of the wedge neck of the wire that has experienced this fatigue failure is shown in Figure 2 .

[0033] The inventors' research has shown that in ultra-low loop-bonded LED devices that have been miniaturized and thinned using conventional silver alloy bonding wires, fatigue failure of the ball neck (the part that stands up in the ball bond with the pad electrode on the LED element) occurs as the main undesirable condition, unlike the conventional high loop-bonded and special loop-bonded LED devices mentioned above. That is, as low looping progresses, there is a tendency for fatigue failure of the wedge neck to decrease and fatigue failure of the ball neck to increase. A photograph of the ball neck of the wire that has produced this fatigue failure is shown in FIG. Figure 3 .

[0034] The present inventors carefully examined the action and state of the bonding wire during wiring in a narrow area in a small LED device, and explored the cause of fatigue failure of the ball neck. As a result, it can be seen that if the bending operation of the wire during wiring increases, the strain is likely to be biased towards the bending, and the strain is particularly likely to be concentrated in the ball neck that has undergone more bending operations. In addition, it can be seen that with the temperature change around the LED element, the stress of thermal expansion and contraction of the seal is difficult to disperse in the ultra-low ring, and is likely to be concentrated in the ball neck. This shows that the concentration of strain in the bending operation and thermal expansion and contraction stress of the seal to the ball neck is one of the causes of fatigue failure of the ball neck. In addition, it can be seen that with the miniaturization of LED devices, there is a tendency for heat dissipation to decrease and the junction temperature (Tj) to increase, thereby exposing the ball neck to high temperature and promoting its fatigue failure. Therefore, the present inventors believe that by improving the heat resistance of the ball neck, in the use of LED devices that have significantly promoted miniaturization and high light flux in recent years, it is possible to meet the requirements for bonding wires with ultra-low rings with a lower ring height than the previous low ring.

[0035] The inventors also conducted a detailed investigation into the reduction in brightness of LED devices caused by the shadow of the bonding wires and found that the brightness of the LED devices can be improved by maintaining the high reflectivity of the wires emitted by the blue LEDs, and the heat resistance of the ball neck when the bonding wires are used can be improved.

[0036] Based on these insights, the inventors have developed a silver alloy bonding wire for LEDs that improves the brightness of LED devices by having high reflectivity for blue light, and also improves the heat resistance of the ball neck even in ultra-low ring bonding, thereby increasing the freedom of wiring design.

[0037] In summary, the object of the present invention is to provide a silver alloy bonding wire for LED and a method for manufacturing the same, wherein the silver alloy bonding wire for LED achieves high reflectivity for blue light and improves the heat resistance of the ball neck even in ultra-low ring-shaped bonding.

[0038] Technical Solution

[0039] That is, the gist of the present invention is as follows.

[0040] [1] A bonding wire for LED, the bonding wire for LED being a bonding wire for a light emitting diode (LED) composed of a silver alloy containing 98% by mass or more of silver, wherein the high temperature / normal temperature strength ratio represented by the following formula (1) is greater than or equal to 0.6 and less than or equal to 0.99, and the elongation at break in a tensile test at 150°C is greater than or equal to 1.5%.

[0041] High temperature / normal temperature strength ratio = (maximum load of tensile test at 150°C) / (maximum load of tensile test at normal temperature) ... (1)

[0042] [2] The LED bonding wire according to [1], wherein the silver alloy contains copper.

[0043] [3] The LED bonding wire according to [1] or [2], wherein the reflectance ratio of blue light having a wavelength of 440 nm to 490 nm represented by the following formula (2) is 2.6 or more.

[0044] Reflectance ratio = (reflectance of blue light of the LED bonding wire) / (reflectance of blue light of a gold wire having a purity of 99.99 mass %) ... (2)

[0045] [4] The LED bonding wire according to any one of [1] to [3], wherein the silver alloy contains copper in an amount of 0.1 mass % to 2.0 mass % in total relative to the total amount of the silver alloy.

[0046] [5] The LED bonding wire according to any one of [1] to [4], wherein the LED bonding wire contains 0.3 mass % or more and 1.0 mass % or less of copper based on the total amount of the LED bonding wire.

[0047] [6] The LED bonding wire according to any one of [1] to [5], wherein the high temperature / normal temperature strength ratio represented by the above formula (1) is 0.7 or more and 0.97 or less.

[0048] [7] The LED bonding wire according to any one of [1] to [6], wherein the reflectance ratio of blue light having a wavelength of 440 nm to 490 nm represented by the above formula (2) is 2.7 or more.

[0049] [8] A method for manufacturing a bonding wire for a light emitting diode (LED) composed of a silver alloy, comprising the following steps: a step of obtaining a silver alloy wire containing 98% by mass or more of silver from a silver alloy material; a step of performing a wire drawing process on the silver alloy wire in stages, the wire drawing process including at least one wire drawing process with a cross-sectional shrinkage rate of 7% or more and 30% or less; and a step of performing a heat treatment on the silver alloy wire, adjusting the high temperature / normal temperature strength ratio represented by the following formula (1) in the bonding wire for the LED to be greater than 0.6 and less than 0.99, and adjusting the elongation at break in a tensile test at 150°C to be greater than 1.5%.

[0050] High temperature / normal temperature strength ratio = (maximum load of tensile test at 150°C) / (maximum load of tensile test at normal temperature) ... (1)

[0051] In addition, in this specification, the symbol "to" represents a numerical range that is greater than or equal to a value on the left side of the symbol and less than or equal to a value on the right side.

[0052] Effects of the Invention

[0053] According to the present invention, a silver alloy bonding wire for LED and a method for manufacturing the same can be provided, wherein the silver alloy bonding wire for LED achieves high reflectivity for blue light and improves the heat resistance of the ball neck even in ultra-low ring bonding.

[0054] According to the present invention, an LED device can be provided, which has improved heat resistance of the ball neck even in ultra-low ring bonding, and can achieve miniaturization and improved brightness by using silver alloy bonding wire with high reflectivity for blue light. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 It is a cross-sectional view schematically showing a high-loop-shaped joined LED device.

[0056] Figure 2 This is a photograph showing fatigue damage of the wedge neck.

[0057] Figure 3 This is a photograph showing fatigue failure of the ball neck.

[0058] Figure 4 It is a cross-sectional view schematically showing the vicinity of the ball neck.

[0059] Figure 5 It is a cross-sectional view schematically showing an LED device according to an embodiment.

[0060] Figure 6 This is a graph showing an SS curve (Stress-Strain curve) in which the vertical axis represents stress σ (MPa) and the horizontal axis represents elongation ε (%), and represents the relationship between stress and elongation in a tensile test.

[0061] Figure 7 It is a schematic diagram for explaining the measurement position of reflectivity.

[0062] Figure 8 1 is a diagram schematically showing a measurement region R of the reflectivity of the bonding wire 72 . DETAILED DESCRIPTION

[0063] Next, embodiments of the present invention will be described.

[0064] The silver alloy bonding wire for LED of the embodiment is a bonding wire mainly composed of silver and used to connect the pad electrode and the lead electrode of the LED element. In other words, the silver alloy bonding wire for LED of the embodiment is a bonding wire for LED composed of a silver alloy.

[0065] In the silver alloy bonding wire for LED of the embodiment, the ratio of the maximum load of the tensile test at 150°C to the maximum load of the tensile test at room temperature, that is, the ratio represented by (maximum load of the tensile test at 150°C) / (maximum load of the tensile test at room temperature) is greater than 0.6 and less than 0.99. Hereinafter, the ratio represented by (maximum load of the tensile test at 150°C) / (maximum load of the tensile test at room temperature) is also referred to as "high temperature / normal temperature strength ratio". In addition, the maximum load of the tensile test at 150°C is also referred to as "high temperature strength", and the maximum load of the tensile test at room temperature is also referred to as "normal temperature strength". The silver alloy bonding wire for LED of the present embodiment has excellent heat resistance by making the "high temperature / normal temperature strength ratio" within the above range, so that, for example, the high heat resistance strength of the ball neck required for the bonding wire for LED used in LCD backlight can be obtained.

[0066] In the silver alloy bonding wire for LED of the embodiment, from the viewpoint of improving the heat resistance strength of the ball neck, the high temperature / normal temperature strength ratio is preferably 0.7 or more and 0.97 or less, and more preferably 0.8 or more and 0.95 or less. If the high temperature / normal temperature strength ratio is too small, the rate of change of the wire strength caused by temperature change will increase, which may reduce the heat resistance strength of the ball neck. In contrast, when the high temperature / normal temperature strength ratio is too large, the reflectivity of the wire is easily reduced due to the excessive amount of alloy elements and impurity elements.

[0067] In the silver alloy bonding wire for LED of the embodiment, from the viewpoint of improving the heat resistance strength of the ball neck, the high temperature strength is preferably 12.0 kgf / mm in terms of the value per unit cross-sectional area (stress value). 2 More preferably 15.0kgf / mm 2 More preferably, 18.0 kgf / mm 2 In this case, since the high temperature / normal temperature strength ratio tends to increase, it is easy to improve the heat resistance strength of the ball neck. The high temperature strength is a stress value, for example, 29.0 kgf / mm 2 the following.

[0068] In the silver alloy bonding wire for LED of the embodiment, from the viewpoint of improving the heat resistance strength of the ball neck, the room temperature strength is preferably 20.0 kgf / mm in terms of the value per unit cross-sectional area (stress value). 2 Above and 30.0kgf / mm 2 Below, more preferably 21.0kgf / mm2 Above and 29.0kgf / mm 2 Below, more preferably 22.0kgf / mm 2 Above and 28.0kgf / mm 2 If the room temperature strength is not too low, it is easy to improve the heat resistance strength of the ball neck. On the other hand, if the room temperature strength is not too high, it is easy to reduce the amount of added elements, thus increasing the reflectivity of the wire.

[0069] In addition, the elongation at break of the silver alloy bonding wire for LED in the tensile test at 150°C (also referred to as "high temperature elongation") is 1.5% or more. The silver alloy bonding wire for LED in the present embodiment has a high temperature elongation of 1.5% or more, so that strain is not easily accumulated in the ball neck even in an environment where the temperature changes from high temperature (about 150°C) to low temperature (about -40°C), and high heat resistance strength of the ball neck can be obtained.

[0070] The elongation at break of the silver alloy bonding wire for LED in the tensile test at 150°C of the embodiment is preferably 1.8% or more, more preferably 2.0% or more. The upper limit of the high temperature elongation is usually 20%. By making the high temperature elongation within the above range, the accumulation of strain in the ball neck is reduced even if the temperature changes, and the excellent heat resistance strength of the ball neck can be obtained. As described below, it is estimated that the wire having the high temperature / normal temperature strength ratio and the high temperature elongation within the above range has a metal structure that can withstand rapid temperature changes.

[0071] The present inventors performed ball bonding using the silver alloy bonding wire of the embodiment and the conventional silver alloy wire, and compared the states of the grains near the ball bonding parts of the silver alloy bonding wires as follows. The cross section of the bonding wire near the ball bonding part parallel to the wire axis was subjected to EBSD analysis to obtain a grain mapping image of the cross section. In the obtained grain mapping image, the tendency of the grain size at the upper and lower parts of the ball neck was compared.

[0072] As a result, it can be seen that in the conventional silver alloy wire, the size and shape of the grains are significantly different above and below the ball neck near the wire center of the cross section near the ball joint (the area containing one-third of the wire diameter of the wire center axis). That is, in the conventional silver alloy wire, the crystal size becomes larger in the area below the ball neck, and the grains of different sizes and shapes are mixed in the area above the ball neck. For example, in the area above the ball neck, in addition to the slender grains with an aspect ratio (the longest length / shortest length of the grains on the image) of more than 5, the range of the area of ​​the grains (the maximum area of ​​the grains on the image - the minimum area) is large.

[0073] In contrast, it can be seen that in the silver alloy bonding wire of the embodiment, there is little difference in the size and shape of the grains at the top and bottom of the ball neck, and the uniformity of the grains is high. In the above-observed image, fine grains with an aspect ratio of 5 or more are not seen near the center of the wire, and the area range of the grains is smaller than that of the conventional silver alloy wire. This is considered to be because, by adjusting the high temperature / normal temperature strength ratio and the high temperature elongation to the above range, the strain accumulated in the metal structure of the wire due to the thermal stress of repeated heating and cooling is appropriately eliminated by recovery or recrystallization during heating, so it is easy to maintain the uniformity of the crystal size of the ball neck, so the generation of cracks in the ball neck caused by thermal stress is suppressed or the propagation speed of the crack is slowed down.

[0074] As previously studied in silver alloy bonding wires for LEDs, it is not possible to maintain high reflectivity and improve the heat resistance of the ball neck only by optimizing the tensile strength at room temperature and high temperature. Therefore, the inventors have repeatedly studied the relationship between the strength at room temperature and the strength at high temperature of Ag alloy wires of various compositions. As a result, the following fact was found: when the strength at room temperature and the strength at high temperature have a prescribed correlation, and the elongation at high temperature is within a prescribed range, the heat resistance of the ball neck is particularly improved even in ultra-low ring bonding.

[0075] In the past, in the manufacture of Ag alloy bonding wires with a wire diameter of 18 μm to 25 μm, for example, the elongation in the tensile test at room temperature of 25°C was adjusted to about 4% by performing a final heat treatment. In contrast, it is known that the maximum load and breaking load in the tensile test when the wire under the same processing conditions is heated to 150°C (high temperature) will vary greatly depending on the composition of the wire. For example, according to the inventors' experiments, in the case of Ag-20% Au alloy with a wire diameter of 25 μm, the maximum load at room temperature is about 10.5 gf, but it is about 8.2 gf at high temperature. In addition, in the case of Ag-2% Pd alloy with the same wire diameter, the maximum load at room temperature is about 10.0 gf, but it stays at about 5.8 gf at high temperature. The high temperature / normal temperature strength ratio, which is digitized as an indicator of the difference between the maximum loads at room temperature and high temperature, represents the rate of change of the wire strength between high temperature and room temperature.

[0076] The maximum load of silver alloy bonding wire for LED is calculated as the maximum value when the bonding wire test piece with a measuring length of 100mm is continuously stretched at a speed of 10mm / min and a load cell rated at 2N until it breaks. Considering the deviation of the measurement results, it is ideal to find the average value of at least three wires for the maximum load. The room temperature maximum load is the maximum load until the wire breaks when the tensile test is performed at room temperature. The room temperature depends on the season and weather, but as long as it is within the range of 15℃ to 28℃, it does not matter if the wire is not directly heated or cooled. The high temperature maximum load is the maximum load until the wire breaks when the sample is kept in a furnace at a temperature of 150℃ (±5℃) for 10 seconds (the length of the soaking zone (heater) of the electric furnace is 49mm) and the tensile test is performed in the furnace in this state. When the tensile test is performed in the furnace, in order to prevent the wire from contacting the soaking zone of the furnace wall, the wire is set so that the gap (interval) between the wire to be measured and the soaking zone of the electric furnace is 2mm or more and 3mm or less. The elongation at break in the tensile test at 150° C. can be calculated as the elongation at which the test piece breaks in the tensile test. The elongation at break is preferably an average value of at least three pieces in consideration of the variation in the measurement results.

[0077] The silver alloy bonding wire for LED of the embodiment can be composed of an Ag alloy in which alloying elements are added to Ag. For the adjustment of the high temperature / normal temperature strength ratio and the high temperature elongation, the adjustment of the type and concentration of the alloying elements in the Ag alloy is one of the effective methods. In order to adjust the high temperature / normal temperature strength ratio to the above range, for example, in order to achieve a high flux of the backlight, the silver alloy bonding wire for LED of the embodiment is preferably composed of an Ag alloy containing copper (Cu), preferably containing 0.1 mass % or more and 2.0 mass % or less of copper relative to the total amount of the silver alloy. Thereby, it is possible to give the bonding wire a high reflectivity to blue light and improve the brightness of the LED device. The amount of Cu added is more preferably 0.3 mass % or more and 1.0 mass % or less, and further preferably 0.4 mass % or more and 0.9 mass % or less. In particular, by making the bonding wire contain copper (Cu) of more than 0.4 mass % and less than 0.9 mass %, it can provide high reflectivity for blue light, and the high temperature / normal temperature strength ratio and high temperature elongation can be adjusted to better values, which can significantly improve the heat resistance of the ball neck.

[0078] The silver alloy bonding wire for LED of the present embodiment can suppress sulfurization of the bonding wire as long as it has the above composition, suppress a decrease in resistance to such temperature changes and stress changes, and deterioration in reflectivity, thereby improving long-term reliability.

[0079] The ratio of the reflectivity of the silver alloy bonding wire for LED of the embodiment for blue light with a wavelength of 440nm to 490nm to the reflectivity of the gold wire with a purity of 99.99% by mass (reflectivity ratio described below) is preferably 2.6 or more, more preferably 2.7 or more, and further preferably 2.8 or more. By adjusting the high temperature / normal temperature intensity ratio within the range of the embodiment and controlling the above reflectivity, a high reflectivity can be achieved, and the heat resistance strength of the ball neck can be effectively improved by a small amount of added elements, and the wire can be manufactured at a low cost.

[0080] The reflectivity ratio of the silver alloy bonding wire for LED of the embodiment to the light of wavelength 440nm to 490nm of the gold wire can be measured as described below. After the silver alloy bonding wire for LED for evaluation is bonded to the bonding evaluation substrate, the surface of the bonded wire is irradiated with light using a white LED lamp to measure the reflectivity. The reflected light from the surface of the wire can be measured using a spectroradiometer, a hyperspectral camera, etc., and the reflectivity of each wavelength can be calculated. In the reflectivity, the reflectivity at the blue emission peak wavelength of the light source is taken as the reflectivity of blue light with a wavelength of 440nm to 490nm. In addition, prepare a gold wire with the same wire diameter as the silver alloy bonding wire for LED to be measured and a gold purity of 99.99% by mass. After the gold wire is bonded to the bonding evaluation substrate, the reflectivity of blue light is measured in the same manner as above, and the reflectivity at the blue emission peak wavelength of the light source is measured. Based on these results, the reflectivity ratio is calculated by the following formula (2).

[0081] Reflectance ratio = (reflectance of blue light of silver alloy bonding wire for LED) / (purity 99.99 quality

[0082] % of the blue light reflectivity of the gold wire)……(2)

[0083] It should be noted that the error of the wavelength of the blue light emission peak of the light source in the above-mentioned reflectivity measurement can be allowed to be ±5nm. In addition, the blue light emission peak wavelength of the light source can be obtained as the wavelength with the highest reflectivity in the blue region when measuring the reflectivity of the white plate. Regarding the reflectivity ratio, considering the deviation of the measurement results, it is ideal to obtain the average value of at least three.

[0084] In the silver alloy bonding wire for LED of the embodiment, from the viewpoint of obtaining high reflectivity, the concentration of silver contained in the Ag alloy is 98 mass % or more, preferably 98.5 mass % or more, more preferably 99 mass % or more, and further preferably 99.1 mass % or more. In addition, from the viewpoint of obtaining higher heat resistance strength of the ball neck, the concentration of silver is preferably 99.9 mass % or less, more preferably 99.7 mass % or less, and further preferably 99.6 mass % or less. If the amount of silver is below the above upper limit, sulfidation can be suppressed and long-term reliability can be improved.

[0085] The silver alloy bonding wire for LED of the embodiment may contain trace additive elements and inevitable impurities in addition to silver and the above-mentioned alloying elements (copper). Preferably, the trace additive elements are Ca, Y, La, Gd, P, Bi, Ge, Al, and Fe, and their amount is 100 mass ppm or less relative to the total amount of the silver alloy. Inevitable impurities are, for example, In, Pb, Si, etc., and their amount is generally 100 mass ppm or less, preferably 50 mass ppm or less relative to the total amount of the silver alloy, calculated in total with the above-mentioned trace additive elements. In order to take into account both the excellent heat resistance and high reflectivity of the ball neck, the silver alloy bonding wire for LED of the embodiment preferably does not contain other elements other than silver, alloying elements (copper) and inevitable impurities. As trace additive elements contained in the silver alloy bonding wire for LED, for example, a high-frequency inductively coupled plasma (ICP) emission spectrometer and an ICP mass spectrometer can be used to analyze the liquid obtained by dissolving the bonding wire of the evaluation object with a strong acid, and the concentration of the elements contained in the bonding wire as a whole can be detected.

[0086] The wire diameter of the silver alloy bonding wire for LED of the embodiment is preferably 15 μm or more and 30 μm or less, more preferably 18 μm or more and 25 μm or less. When the wire diameter of the bonding wire is thin, the brightness of the LED device can be improved. According to the silver alloy bonding wire for LED of the embodiment, even such a thin wire has excellent heat resistance of the ball neck, so it is suitable for thinning. Therefore, it can be preferably used for miniaturized and thin LED devices that require high flux. For example, when using the previous silver alloy bonding wire, it is necessary to design the height (h) of the bonding ring to be at least 4 to 5 times the wire diameter, but by using the silver alloy bonding wire for LED of the present embodiment, the ring height (h) can be designed to be less than 3 times the wire diameter. In addition, even in such an ultra-low ring shape, due to the strong heat resistance and impact resistance, the yield rate of the manufactured LED device can be improved, and mass production is easy, which is advantageous in terms of cost. Furthermore, the silver alloy bonding wire for LED according to the embodiment can achieve long-term reliability even when used in a harsh environment such as a car navigation device or a driving recorder. Figure 4 As shown, the ring height (h) refers to the height from the upper portion 40 of the ball where the ball engages to the highest portion 41 of the ring.

[0087] [Method for manufacturing silver alloy bonding wire for LED]

[0088] Next, the method for manufacturing the silver alloy bonding wire for LED of the embodiment is described. The method for manufacturing the silver alloy bonding wire for LED of the embodiment comprises: a step of preparing an Ag alloy material; a step of obtaining an Ag alloy wire from the Ag alloy material; a wire drawing step of drawing the Ag alloy wire; and a heat treatment step of heat treating the Ag alloy wire.

[0089] (Process for producing Ag alloy material)

[0090] Ag or an Ag alloy of a specified purity is melted together with an alloying element of a target composition, thereby obtaining an Ag alloy material. The melting can be performed using a heating furnace such as an arc heating furnace, a high-frequency heating furnace, a resistance heating furnace, or a continuous casting furnace. In order to prevent the mixing of oxygen from the atmosphere, it is preferred that the upper part of the silver melt in the heating furnace be kept in a vacuum or an inert gas atmosphere such as argon or nitrogen.

[0091] (Step of Obtaining Ag Alloy Wire)

[0092] The molten Ag alloy material is cast and solidified in a heating furnace in a manner to have a predetermined wire diameter to obtain an Ag alloy wire, or the molten Ag alloy material is cast in a mold to make an ingot, and the ingot is drawn into a predetermined wire diameter to obtain an Ag alloy wire.

[0093] The obtained Ag alloy wire is drawn to a final wire diameter and heat-treated as necessary to produce an Ag alloy bonding wire. The wire drawing and heat treatment are preferably performed in stages during the wire drawing process.

[0094] (Wire drawing process)

[0095] The processing rate of wire drawing is determined according to the final wire diameter, purpose, etc. of the silver alloy bonding wire for LED to be manufactured. As the total processing rate until the Ag alloy wire is processed into the final wire diameter, the processing rate of wire drawing is preferably 90% or more and 99.99% or less. The processing rate can be calculated as the reduction rate of the cross-sectional area of ​​the wire. The wire drawing process preferably uses multiple diamond dies to reduce the wire diameter in stages. In this case, the cross-sectional reduction rate (processing rate) of each diamond die is preferably 7% or more and 30% or less. In addition, since the smoothness of the wire surface will affect the reflectivity, it is preferred to use a single crystal diamond die starting from the specified wire diameter.

[0096] (Heat treatment process)

[0097] Preferably, the Ag alloy wire is drawn to the final wire diameter before heat treatment. For example, the temperature and time of the heat treatment are preferably determined while considering the characteristics required for the bonding wire. In addition, the heat treatment can also be performed at any stage of the online manufacturing (drawing process) according to the purpose.

[0098] As for heat treatment, mobile heat treatment in which the wire is passed through a heating atmosphere heated to a predetermined temperature for heat treatment is preferred because the heat treatment conditions can be easily adjusted. In the case of mobile heat treatment, the heat treatment time can be calculated by the passing speed of the wire and the passing distance of the wire in the heating container. As a heating container, an electric furnace is used. Preferably, heat treatment is performed in a tubular electric furnace in a gas atmosphere of nitrogen (N2) gas or a small amount of hydrogen (H2) gas mixed in nitrogen (N2) gas.

[0099] As a method for manufacturing the silver alloy bonding wire for LED of the present embodiment, for example, a wire drawing process with a cross-sectional shrinkage rate of 7% or more and 30% or less is performed in the wire drawing process, and a heat treatment is performed after the wire drawing process is completed. The heat treatment temperature is set to be slightly lower than the heat treatment temperature of the usual silver alloy wire. Specifically, the heat treatment method is as follows: if the length of the electric furnace (heat equalization part) is 530 mm, the temperature in the electric furnace is 200°C or more and 500°C or less, and the wire feed speed is 30 m / min or more and 80 m / min or less. In this way, a silver alloy bonding wire for LED having a high temperature / normal temperature strength ratio and a high temperature elongation within the above range can be obtained.

[0100] [LED devices]

[0101] Next, an LED device using the silver alloy bonding wire for LED according to the embodiment will be described. Figure 5 It is a cross-sectional view schematically showing an LED device 50 according to an embodiment.

[0102] Figure 5 The LED device 50 shown has a package substrate 59, an LED element 51 provided on the package substrate 59, a bank 56 surrounding the LED element 51, a bonding wire 53, and a pair of pad electrodes 521, 522 provided on the LED element 51. The LED device 50 also has lead electrodes 581, 582, and the bank 56 and the lead electrodes 581, 582 form a concave portion with the bank 56 as a side surface and the lead electrodes 581, 582 as a bottom surface, and the LED element 51 is placed on the bottom surface of the concave portion via an adhesive layer 57. The lead electrodes 581, 582 are formed of aluminum or the like, and are bonded to the package substrate 59 by silver paste or the like. The pad electrodes 521, 522 are formed of gold (Au) or the like, and the pair of pad electrodes 521, 522 and the lead electrodes 581, 582 are electrically connected to each other at corresponding electrodes via bonding wires 53. The LED element 51 is covered by a sealing member 54.

[0103] The bonding wire 53 is composed of the silver alloy bonding wire for LED of the above embodiment, and the preferred embodiment is also as described above. Since the silver alloy bonding wire for LED of the above embodiment is used, the ring height (h) can be designed to be less than 3 times of the wire diameter, and the LED device 50 can be made smaller and thinner. The LED element 51 is, for example, a nitride semiconductor (In X Al Y Ga 1-X-Y N, 0≤X, 0≤Y, X+Y≤1) as a blue LED element of the light emitting semiconductor layer. The LED element 51 emits light in the short wavelength region of visible light, i.e., in the wavelength range of 380nm to 485nm, and preferably has a light emission peak wavelength (maximum light emission wavelength) in the wavelength range of 420nm to 485nm, more preferably in the wavelength range of 440nm to 480nm.

[0104] The seal 54 is, for example, a thermosetting resin such as epoxy resin, silicone resin, epoxy-modified silicone resin, or modified silicone resin. The seal 54 contains a phosphor (not shown) that converts the wavelength of light from the LED element 51. Examples of the phosphor include yttrium aluminum garnet phosphor (YAG:Ce) activated with cerium; lutetium aluminum garnet phosphor (LAG:Ce) activated with cerium; nitrogen-containing calcium aluminosilicate phosphor (CaO-Al2O3-SiO2) activated with europium and / or chromium; silicate phosphor ((Sr,Ba)2SiO4) activated with europium; nitride phosphors such as β-silicon aluminum oxynitride ceramic phosphor, CASN phosphor, and SCASN phosphor; KSF phosphor (K2SiF6:Mn); sulfide phosphor, and quantum dot phosphor. By combining these phosphors with a blue light-emitting element or an ultraviolet light-emitting element, white light emission can be obtained.

[0105] Example

[0106] Next, examples will be described. The present invention is not limited to the following examples.

[0107] As the raw material of the bonding wire, a high-purity raw material with a purity of 99.99 mass % or more is used for Ag as a main component, and raw materials with a purity of 99.99 mass % or more for Pd, Cu, and Au as additive elements and 99.999% or more for other elements.

[0108] As described above, an Ag alloy material containing a specified alloying element is prepared, and an Ag alloy wire raw material having a wire diameter of several mm is obtained by continuous casting. Next, the Ag alloy wire raw material is subjected to wire drawing and heat treatment using cold die drawing. In the wire drawing process, the cross-sectional shrinkage rate (processing rate) of each diamond die head is greater than 7% and less than 30%. In addition, in the embodiment, the total processing rate until the final wire diameter is processed is greater than 90% and less than 99.99%, and a single crystal diamond die head is used from a specified wire diameter (e.g., 400 μm). In the comparative example, the total processing rate until the final wire diameter is processed is less than 90% or greater than 99.999%, and a single crystal diamond is used after a specified wire diameter (e.g., 50 μm). The final wire diameter after the wire drawing process is 15 μm to 25 μm.

[0109] Regarding heat treatment, the final heat treatment temperature in the examples is 200° C. to 500° C., and in the comparative examples is 350° C. to 600° C. In addition, the heat treatment atmosphere uses a gas (N2+H2) in which a small amount of hydrogen is mixed with nitrogen or nitrogen (N2).

[0110] [Analysis of components contained in bonding wire]

[0111] The concentration of components contained in the bonding wire (other than inevitable impurities) can be detected as the concentration of elements contained in the entire bonding wire by analyzing a liquid obtained by dissolving the bonding wire to be evaluated in a strong acid using an ICP emission spectrometer or an ICP mass spectrometer.

[0112] [Maximum load at normal and high temperatures]

[0113] The maximum load is explained. When a tensile test, which is one of the tests for measuring the mechanical properties of a wire, is performed, if the force that stretches the wire is increased, the wire will deform. The force that stretches the wire in a tensile test is generally referred to as "Stress", "σ", "load", "endurance", "stress", etc. In addition, the deformation of the wire is generally referred to as "Strain", "ε", "strain", "elongation", etc. In this specification, the force that stretches the wire in a tensile test is referred to as "stress" and is represented by the symbol σ. In addition, the deformation of the wire is referred to as "elongation" and is represented by the symbol ε. A graph that represents the relationship between stress and elongation in the tensile test with stress σ (MPa) on the vertical axis and elongation ε (%) on the horizontal axis is the SS curve (Stress-Strain curve). Figure 6 The graph of is an example of a graph of the SS curve. The maximum load of the line in this embodiment is the tensile force at point S1 in the graph of the SS curve, and the elongation at break is the ratio of the elongation between the points of the tensile test piece at point S2 to the original distance between the points.

[0114] The maximum load in the tensile test can be measured by a tensile test device. The maximum load is calculated as the maximum value when the bonding wire with a length of 100 mm is continuously stretched to break at a speed of 10 mm / min, a load sensor rated at 2 N, and a full scale of 10% in a tensile test device (for example, Autocom, model: AC-20CT-M manufactured by TSE Co., Ltd.). The load or stress here is the force applied to the wire stretched at the above speed, and is usually automatically calculated by converting the tensile force into an electrical signal by a load cell. Taking into account the deviation of the measurement results, the maximum load is calculated as the average value of three wires.

[0115] Next, the temperature environment in the tensile test is described. The room temperature maximum load (room temperature strength) of the bonding wire of the present invention is the maximum load until the wire breaks when a tensile test is performed on a sample with a length of 100 mm at a room temperature of 15°C to 28°C as described above. In addition, the high temperature maximum load (high temperature strength) of the bonding wire is the maximum load until the heated part of the wire breaks when a sample with a length of 100 mm is heated to 150°C in a furnace, kept in a furnace at 150°C for 10 seconds, and then subjected to a tensile test in the furnace. Using the room temperature strength and high temperature strength obtained above, the high temperature / room temperature strength ratio of the bonding wire of the embodiment and the comparative example is calculated. The high temperature / room temperature strength ratio is calculated by averaging three values ​​and discarding the third decimal place.

[0116] [High temperature elongation]

[0117] In the tensile test for measuring the maximum load at high temperature, the elongation at which the wire breaks is measured as the high temperature elongation. Taking into account the variation in the measurement results, the high temperature elongation is calculated by averaging three values ​​and discarding the second decimal place.

[0118] [Reflectivity ratio]

[0119] After bonding 20 wires in total, one each for evaluation of the embodiment and comparative example, on a bonding evaluation substrate, the surface of each wire after bonding was irradiated with a general-purpose white LED light, and the reflectivity at the wavelength of 460nm, the peak wavelength of blue light emission of the general-purpose white LED light, was measured using a hyperspectral camera NH-6TND manufactured by EVA JAPAN Co., Ltd. Figure 7 A diagram for explaining the measurement location of the reflectance is shown. Figure 7 The bonding wire 72 in which the ball is bonded to the pad electrode 71 is schematically shown. The reflectance of the bonding wire is measured at a location approximately in the center of the portion where the bonding wire 72 forms a loop parallel to the substrate ( Figure 7The vicinity of point P is photographed using an optical microscope equipped with a hyperspectral camera NH-6TND manufactured by EVA JAPAN Co., Ltd., using a 150x objective lens. The 100 pixel × 100 pixel range of the approximate center of the image captured using a dedicated application for the hyperspectral camera is used as the measurement area. Figure 8 The measurement area R of the reflectivity of the bonding wire 72 is schematically shown. Figure 7 and Figure 8 In the figure, the arc and two lines on the bonding line 72 indicate that the lengths of the parts marked with the arc and the two lines in each figure are equal to each other. The blue emission peak wavelength of a general white LED lamp is the blue emission wavelength with the highest reflectivity in the reflectivity measurement of a white plate (standard sample). Similarly, the reflectivity of a gold wire with a gold purity of 99.99% by mass and the same wire diameter as in each example is measured, and the above formula (2) is used as the reflectivity ratio. Taking into account the deviation of the measurement results, the reflectivity ratio is calculated by finding the average of three wires and discarding the third decimal place. A reflectivity ratio of 2.8 or more is evaluated as ◎ (excellent), a reflectivity ratio of 2.7 or more and less than 2.8 is evaluated as ○ (good), a reflectivity ratio of 2.6 or more and less than 2.7 is evaluated as Δ (acceptable), and a reflectivity ratio of less than 2.6 is evaluated as × (unacceptable).

[0120] [Thermal shock test of ball neck]

[0121] 40 wires of each bonding wire used for evaluation of the embodiment and comparative example were bonded to the bonding evaluation substrate at a loop height of 3 times the wire diameter. Using a commercially available gas phase thermal shock device, the bonding evaluation substrate after bonding was subjected to a thermal shock test of 500 cycles, wherein one cycle consisted of holding at -40°C for 15 minutes and holding at 150°C for 15 minutes. After 500 cycles of thermal shock test, a hook was set at a position based on 5% to 8% of the loop length from the ball bonding, and a pulling test was performed by stretching the hook until it broke. The inner diameter of the hook used here was 4 to 6 times the wire diameter, and the pulling speed was a constant speed of 250μm / s. In the pulling test, there were wires that broke at the location where the hook was set, but in this test, the fracture rate at the ball neck where the strength was weakened due to multiple bending operations was counted. For each bonding wire used for evaluation of the embodiments and comparative examples, if the fracture incidence rate at the ball neck is 70% or less, it is considered that the resistance to the thermal shock test is good and is evaluated as ◎. If it is more than 70% and less than 85%, it has sufficient resistance and is evaluated as ○. If it is more than 85%, there is a possibility of adverse conditions in practical use and is evaluated as ×.

[0122] [Heat resistance test of ball neck]

[0123] 75 bonding wires of each embodiment and comparative example used for evaluation were bonded to a bonding evaluation substrate at a loop height of 3 times the wire diameter. Using a vibration tester, the bonding evaluation substrate was subjected to vibration at a frequency of 30 Hz, a vibration time of 1 minute, and an amplitude of 2 times the wire diameter, and then heated at 150°C for 15 minutes. The excitation and heating were regarded as one cycle, and the tensile strength of the 75 ball necks was measured after 10 cycles and 20 cycles. When the tensile strength reached 1g or less, it was judged as "broken", and the fracture incidence was counted. For each bonding wire used for evaluation of the embodiment and comparative example, if the fracture incidence after 10 cycles was 20% or more, there was a possibility of a practical problem, so it was evaluated as × and no further testing was performed. If the fracture incidence after 10 cycles was less than 20%, the number of cycles was further increased, and the test was performed up to 20 cycles. If the fracture occurrence rate after 20 cycles is 5% or less, the heat resistance of the ball neck is considered to be good and is evaluated as ◎. If the fracture occurrence rate after 20 cycles is 20% or less, the heat resistance of the ball neck is sufficient and is evaluated as ○.

[0124] [Comprehensive evaluation]

[0125] For each bonding wire used for evaluation of the embodiments and comparative examples, in the comprehensive evaluation, the bonding wire with a reflectivity of ◎ or ○ and a result of the heat resistance strength test of the ball neck of ◎ or ○ was very good and was therefore recorded as "A", and the bonding wire with a reflectivity of Δ and a result of the heat resistance strength test of the ball neck of ◎ or ○ was recorded as "B" due to its sufficient performance, and the rest was recorded as unqualified "C".

[0126] The above results are shown in Table 1. It should be noted that in the table, the gas (N2+H2) in the heat treatment gas is recorded as "N2H2", and the nitrogen gas is recorded as "N2". In addition, Comparative Example 1 is a silver wire with a purity of 99.99 mass % or more, and the blank columns for the added elements and trace added elements indicate that the elements are not contained.

[0127] [Table 1]

[0128]

[0129] As shown in Table 1, according to the silver alloy LED bonding wire containing more than 98% by mass of silver, a high temperature / normal temperature strength ratio of 0.6 to 0.99, and a high temperature elongation of 1.5% or more, a high reflectivity of blue light can be achieved, and a higher heat resistance strength of the ball neck can be obtained. In the previous silver alloy bonding wire, in order to prevent the destruction of the ball neck in an attempt to maintain a sufficient reflectivity of the LED, it is necessary to design the ring height (h) of the LED to be at least 4 to 5 times the wire diameter. In contrast, according to the silver alloy LED bonding wire of each embodiment, due to the high reflectivity of blue light, a high reflectivity of the LED to light can be achieved, and a higher heat resistance strength of the ball neck can be obtained. Therefore, the ring height (h) can be designed to be less than 3 times the wire diameter, which can further promote the miniaturization and thinning of the LED device. In addition, according to the silver alloy LED bonding wire of the embodiment, the heat resistance strength of the ball neck is excellent, so it can be further thinned, which is also suitable for improving the brightness of the LED.

[0130] Industrial Applicability

[0131] The present invention can be used for bonding of LEDs, and can be used for bonding of LED devices that are particularly being miniaturized and thinned.

Claims

1. A bonding wire for LED, characterized in that: The LED bonding wire is a bonding wire for a light emitting diode (LED) made of a silver alloy containing 98% by mass or more of silver. The high temperature / normal temperature strength ratio represented by the following formula (1) is 0.6 or more and 0.99 or less, the elongation at break in a tensile test at 150°C is 1.5% or more, High temperature / normal temperature strength ratio = (maximum load of tensile test at 150°C) / (maximum load of tensile test at normal temperature) (1).

2. The LED bonding wire according to claim 1, wherein The silver alloy includes copper.

3. The LED bonding wire according to claim 1 or 2, wherein: The reflectance ratio of blue light with a wavelength of 440 nm to 490 nm represented by the following formula (2) is 2.6 or more. Reflectance ratio=(reflectance of blue light of the LED bonding wire) / (reflectance of blue light of a gold wire having a purity of 99.99 mass%) (2).

4. The LED bonding wire according to claim 1 or 2, wherein: The silver alloy contains copper in an amount of 0.1 mass % or more and 2.0 mass % or less relative to the total amount of the silver alloy.

5. The LED bonding wire according to claim 1 or 2, wherein: The light emitting diode bonding wire contains 0.3 mass % or more and 1.0 mass % or less of copper based on the total amount of the light emitting diode bonding wire.

6. The LED bonding wire according to claim 4, wherein The high temperature / normal temperature strength ratio represented by the above formula (1) is 0.7 or more and 0.97 or less.

7. The LED bonding wire according to claim 4, wherein The reflectance ratio of blue light having a wavelength of 440 nm to 490 nm represented by the above formula (2) is 2.7 or more.

8. A method for manufacturing a bonding wire for LED made of a silver alloy, comprising the following steps: A step of obtaining a silver alloy wire containing 98 mass % or more of silver from a silver alloy material; A wire drawing process of performing wire drawing on the silver alloy wire in stages, wherein the wire drawing process includes at least one wire drawing process with a cross-sectional reduction rate of 7% or more and 30% or less; and The heat treatment process of heat treating the silver alloy wire, The high temperature / normal temperature strength ratio represented by the following formula (1) in the LED bonding wire is adjusted to 0.6 or more and 0.99 or less, and the elongation at break in a tensile test at 150° C. is adjusted to 1.5% or more, High temperature / normal temperature strength ratio = (maximum load of tensile test at 150°C) / (maximum load of tensile test at normal temperature) (1).

Citation Information

Patent Citations

  • Bonding wire

    JP2012099577A

  • Bonding wire for semiconductor devices

    JP2013110410A

  • Bonding wire

    JP2014096403A